2016
DOI: 10.5500/wjt.v6.i4.620
|View full text |Cite
|
Sign up to set email alerts
|

Organ transplantation and drug eluting stents: Perioperative challenges

Abstract: Patients listed for organ transplant frequently have severe coronary artery disease (CAD), which may be treated with drug eluting stents (DES). Everolimus and zotarolimus eluting stents are commonly used. Newer generation biolimus and novolimus eluting biodegradable stents are becoming increasingly popular. Patients undergoing transplant surgery soon after the placement of DES are at increased risk of stent thrombosis (ST) in the perioperative period. Dual antiplatelet therapy (DAPT) with aspirin and a P2Y12 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 83 publications
(102 reference statements)
0
6
0
4
Order By: Relevance
“…Em torno de 64,4% dos pacientes que apresentam essa complicação vascular desenvolvem infarto do miocárdio e outros 8,9% chegam a óbito. Valores preocupantes ainda são encontrados quando se compara a mortalidade nos primeiros seis meses após procedimento, onde taxas de 20,8% são encontradas (Dalal, 2016).…”
Section: Terapia Com Stents Convencionaisunclassified
See 3 more Smart Citations
“…Em torno de 64,4% dos pacientes que apresentam essa complicação vascular desenvolvem infarto do miocárdio e outros 8,9% chegam a óbito. Valores preocupantes ainda são encontrados quando se compara a mortalidade nos primeiros seis meses após procedimento, onde taxas de 20,8% são encontradas (Dalal, 2016).…”
Section: Terapia Com Stents Convencionaisunclassified
“…As plataformas usuais são constituídas de aço inoxidável ou ligas metálicas, de comprimento diferenciado, que é definido pelo tamanho da lesão que pode ser corrigida, de forma que a extensão da lesão não ultrapasse o tamanho do stent. Essa base é recoberta por uma camada polimérica durável cuja função é de transportar e permitir a liberação controlada diretamente sobre a lesão no vaso-alvo, com reduzidas concentrações sistêmicas, visando à redução dos efeitos colaterais sistêmicos (Dalal, 2016).…”
Section: Terapia Com Stents Farmacológicosunclassified
See 2 more Smart Citations
“…Implant materials, including vascular stents, directly contact blood, and wall tissues in vivo , which can cause mechanical strain and damage to the implant site. In clinical trials, surface properties of the implant material have been shown to slow endothelialization and cause restenosis and thrombosis . Therefore, more studies are needed to improve our understanding of the surface properties of implant materials, particularly those aimed at developing surface modification strategies that accelerate endothelialization.…”
Section: Introductionmentioning
confidence: 99%